2020
DOI: 10.2196/19630
|View full text |Cite|
|
Sign up to set email alerts
|

Global Changes and Factors of Increase in Caloric/Salty Food Intake, Screen Use, and Substance Use During the Early COVID-19 Containment Phase in the General Population in France: Survey Study

Abstract: Background The international outbreak of coronavirus disease (COVID-19) has led many countries to enforce drastic containment measures. It has been suggested that this abrupt lockdown of populations will foster addiction-related habits such as caloric/salty food intake, screen use, and substance use. Objective Our aim was to assess the global changes and factors of increase in addiction-related habits during the early COVID-19 containment phase in Franc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
277
6
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(323 citation statements)
references
References 26 publications
31
277
6
9
Order By: Relevance
“…Social isolation with or without loneliness and boredom can be associated with a negative impact on nutrition habits, obesity, physical activity, and poor physical and mental health [ 6 , 15 , 18 , 20 , 21 ]. Some authors showed that high-level of depression was related to poor diet, increased intake of saturated fat, energy-dense and salty foods [ 6 , 22 ]. Women who tended to act impulsively in a stressing environment were more likely to eat more candies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social isolation with or without loneliness and boredom can be associated with a negative impact on nutrition habits, obesity, physical activity, and poor physical and mental health [ 6 , 15 , 18 , 20 , 21 ]. Some authors showed that high-level of depression was related to poor diet, increased intake of saturated fat, energy-dense and salty foods [ 6 , 22 ]. Women who tended to act impulsively in a stressing environment were more likely to eat more candies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together with the changes in diet, a strong impact of quarantine on physical activity was observed. Many studies showed that all levels of physical activity decreased and sitting or screen time increased [ 12 , 15 , 16 , 17 , 18 , 22 , 24 ]. Few studies found opposite results, showing an increase of physical activity during COVID-19 crisis [ 16 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Decrease the intake of unhealthy foods and drinks (e.g., ultra-processed, refined carbohydrates, added sugars, and fats) periods lead to increases in sedentary behavior (unhealthy) food consumption, alcohol consumption, tobacco use, stress, and decreased well-being (96)(97)(98). Distressingly, increased food consumption and snacking are more prevalent in people with overweight or obesity.…”
Section: Dietmentioning
confidence: 99%
“…There was one study from France, however, which found an increase in cannabis use among 31.2% (195 of 620) of regular cannabis users making up 5.44% (620 of 11,391) of total participants, increased usage. 49…”
Section: Other Harmful Substancesmentioning
confidence: 99%